Editorial: UK quality of care drive improving ulcerative colitis hospital outcomes. Issue 5 (14th August 2019) - Moore, Gregory
Abstract : LINKED CONTENT This article is linked to Shawihdi et al and Bodger papers. To view these articles, visit https://doi.org/10.1111/apt.15315 and https://doi.org/10.1111/apt.15444 .